The Modification Formula of Manggaraian Traditional Food â€œRebok Sikisekoâ€ - Chelsia Wihelmina Edam; A.A Made Semariyani; Ni Made Ayu Suardani Singapurwa (Warmadewa University Press, 2019)
This study aims to determine the effect of comparison of corn flour and grated coconut and the addition of liquid margarine to the characteristics of